2021
DOI: 10.3390/ijerph18116087
|View full text |Cite
|
Sign up to set email alerts
|

Estimating Service Demand for Intermediary Care at a Community Integrated Intermediary Care Center among Family Caregivers of Older Adults Residing in Chiang Mai, Northern Thailand

Abstract: Background: Thailand’s population is currently the third most rapidly aging in the world, with an estimated 20 million ageing population by 2050. Sustainability of the family based long-term care model is challenged by the chronic burden on family caregivers and by smaller family sizes. We aimed to introduce a new service model, Community Integrated Intermediary Care (CIIC), TCTR20190412004, including free of charge intermediary care services at CIIC centers in the local community, to help older adults whose c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 6 publications
(10 citation statements)
references
References 33 publications
0
10
0
Order By: Relevance
“…Moreover, caregiver burden measurement of the family caregivers can be applied as a screening tool to assess long-term care needs, complementing the routine dependency assessment of care recipients using ADL scoring [ 11 , 14 ]. In many developing countries, studies increasingly have reported the long-term care need among older persons [ 34 , 35 ].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Moreover, caregiver burden measurement of the family caregivers can be applied as a screening tool to assess long-term care needs, complementing the routine dependency assessment of care recipients using ADL scoring [ 11 , 14 ]. In many developing countries, studies increasingly have reported the long-term care need among older persons [ 34 , 35 ].…”
Section: Discussionmentioning
confidence: 99%
“…The CIIC model is a novel prevention-based, long-term care model created to enhance the family-based long-term care system (Fig. 2 ) which has traditionally been practised in Thailand and its neighbouring Asian countries as well as many low- and middle-income countries globally [ 14 , 29 ]. Conceptually, it is a combination of formal care and informal care in a district, subdistrict or a city.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…This study explored which sociodemographic features may influence this phenomenon. Previous research has pointed out features that have an impact on the demand for social services [ 36 , 37 , 38 , 39 ]. Therefore, we analyzed demographic and economic data divided geographically by CSS coverage area.…”
Section: Introductionmentioning
confidence: 99%